Pediatric uveitis: Role of the pediatrician - Shivpuri, Abhay; Turtsevich, Inga; Solebo, Ameenat Lola; Compeyrot-Lacassagne, Sandrine (Frontiers in Pediatrics, 2022)
The challenges of childhood uveitis lie in the varied spectrum of its clinical presentation, the often asymptomatic nature of disease, and the evolving nature of the phenotype alongside normal physiological development. These issues can lead to delayed diagnosis which can cause significant morbidity and severe visual impairment. The most common ocular complications include cataracts, band keratopathy, glaucoma, and macular oedema, and the various associated systemic disorders can also result in extra-ophthalmic morbidity. Pediatricians have an important role to play. Their awareness of the various presentations and etiologies of uveitis in children afford the opportunity of prompt diagnosis before complications arise. Juvenile Idiopathic Arthritis (JIA) is one of the most common associated disorders seen in childhood uveitis, but there is a need to recognize other causes. In this review, different causes of uveitis are explored, including infections, autoimmune and autoinflammatory disease. As treatment is often informed by etiology, pediatricians can ensure early ophthalmological referral for children with inflammatory disease at risk of uveitis and can support management decisions for children with uveitis and possible underling multi-system inflammatory disease, thus reducing the risk of the development of irreversible sequelae.